2003
DOI: 10.1093/cdj/38.4.310
|View full text |Cite
|
Sign up to set email alerts
|

Do community-based arts projects result in social gains? A review of the literature

Abstract: Arts projects have become an important part of community development strategies. In addition to any creative achievements, projects are expected to have positive and measurable impacts on local social capital. Evidence for this is routinely demanded by funding organisations, and formal evaluations of projects have become a condition of investment. However, quantifying the impact of the arts in terms of social gain presents considerable difficulties, arguably greater than in any other field of evaluation. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 6 publications
2
64
0
5
Order By: Relevance
“…The British based children"s charity, Barnardos, concluded that "arts projects have become an important part of community development strategies" (Newman et al 2001). In particular community arts practice is expected to have significant impacts on the generation of local social capital (Kay and Watt 2000).…”
Section: Community Arts and Developmentmentioning
confidence: 99%
“…The British based children"s charity, Barnardos, concluded that "arts projects have become an important part of community development strategies" (Newman et al 2001). In particular community arts practice is expected to have significant impacts on the generation of local social capital (Kay and Watt 2000).…”
Section: Community Arts and Developmentmentioning
confidence: 99%
“…4,10 Art can affect major determinants of health, including the physical environment, education and skills, employment, community cohesion, social exclusion, and access to services. [11][12][13][14] Sydenham Garden is a primary-carebased STH and participatory arts rehabilitation project for people with significant mental and/or physical illness. Unlike its inspiration, the Blackthorn Trust, 15 it does not have an underlying anthroposophical approach to therapeutic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement in community creative arts can, in itself, have a sustained and positive impact on the mental and social wellbeing of participants (Argyle and Bolton 2005), support the inclusion of marginalized populations (Maidment and Macfarlane 2011), and be a vehicle for community development and social cohesion (Clover 2007;Newman et al 2003). It is, in fact, the central focus of this special issue.…”
Section: Rationale For Alternative Instructional Spaces and Methods Fmentioning
confidence: 98%